2018
DOI: 10.1186/s12864-018-4986-1
|View full text |Cite
|
Sign up to set email alerts
|

Iron-dependent essential genes in Salmonella Typhimurium

Abstract: BackgroundThe molecular mechanisms underlying bacterial cell death due to stresses or bactericidal antibiotics are complex and remain puzzling. Due to the current crisis of antibiotic resistance, development of effective antibiotics is urgently required. Previously, it has been shown that iron is required for effective killing of bacterial cells by numerous bactericidal antibiotics.ResultsWe investigated the death or growth inhibition of S. Typhimurium under iron-restricted conditions, following disruption of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…viability). They are usually defined operationally in natural or specific conditions ( Karash and Kwon, 2018 ) with those genes required for basic metabolism or growth in the natural host or environment identified as essential ( Tateishi et al , 2020 ). Genes required for specific biological processes like motility, drug resistance, cell division etc.…”
Section: Introductionmentioning
confidence: 99%
“…viability). They are usually defined operationally in natural or specific conditions ( Karash and Kwon, 2018 ) with those genes required for basic metabolism or growth in the natural host or environment identified as essential ( Tateishi et al , 2020 ). Genes required for specific biological processes like motility, drug resistance, cell division etc.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the natural transformation was inhibited by adding 100 μM Dip, and the transformation frequency was restored gradually by the supplementation with Fe(NO 3 ) 3 . Dip is reported to be a chelator of divalent cations, which has been widely used in many studies to foster iron starvation ( Lu et al, 2013 ; Yan et al, 2013 ; Karash and Kwon, 2018 ). It was suggested that the natural transformation of R. anatipestifer ATCC11845 could be affected by iron, implying that energy generation, as well as nucleotide synthesis, are important for the process of natural transformation.…”
Section: Discussionmentioning
confidence: 99%
“…The relative changes in abundance of each transposon mutant before and after the treatment reflects the contribution of each gene to survival and adaptation to a particular environment. TIS has been successfully used in various bacteria species to define genetic requirements for bacterial viability and fitness during in vitro growth and following infection of mammalian hosts and host cells [25][26][27][28][29][30][31][32][33]. Our findings delineate the fitness landscapes of GEC P125109 and CEAC D7795 during conditions relevant to mammalian host infection.…”
Section: Introductionmentioning
confidence: 91%